First Language Acquisition of Aitchison's Early Childhood Perspective (Psycholinguistic Studies) - Harun, Uhame Binti; Ritonga, Murni Sari; Hakiki, Kifah (Proceeding of International Conference on Islamic Education (ICIED); Vol 4 No 1 (2019): Proceeding of International Conference on Islamic Education (ICIED), 2019)
Communication using language is very important in everyday life. Communication aims to convey the widest possible information as clearly as one needs with others. Psycholinguistics as one of the complex branches of linguistics, trying to understand how the language process in the human brain. The purpose of this study is to describe in detail the phenomenon of early childhood acquisition in everyday life from Aitchison's perspective. This research is a research library using descriptive qualitative method. Data obtained from several written sources such as; books, journals, articles related to the discussion. The results of this study indicate that the language development according to Aitchison consists of ten stages, namely: 1) the age of 0.3 years can begin to answer, 2) the age of 0.9 years begins to sound intonation patterns, 3) the age of 1.0 years can start making sentences one word, 4) 1.3 years old thirst for words, 5) 1.8 years old master two-word sentences, 6) 2.0 years old can make four-word sentences , can make negative sentences, can master inflection and vocal pronunciation is perfect, 7) age 3,6 years consonant pronunciation starts perfect, 8) age of 4.0 years of sentence mastery is correct, but still limited, 9) age of 5.0 years morphological construction is complete and 10) age of 10, 0 years have matured talking